IMPLEMENTATION OF THE EDUSCRUM METHODOLOGY INTO THE EDUCATIONAL PROCESS - Fendo , Olena (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2024)
The evolution and essence of the Scrum methodology have been succinctly examined, and the possibility of integrating EduScrum into the educational process to enhance the quality of education by improving teaching methods has been analyzed. The key aspects of EduScrum, including the distribution of roles within the project team, sprint planning, and artifacts, have been highlighted. It has been determined that the implementation of the EduScrum methodology in the educational process will contribute to the personal development of education seekers, their engagement in conscious and active participation in learning, as well as the development of relevant soft skills competencies.